KEBIJAKAN KOMUNIKASI MULTIKULTURAL DI MEDIA TELEVISI INDONESIA: KONTROL PEMERINTAH TERHADAP IMPERIALISME BUDAYA - Muntadliroh - (BPSDMP Kominfo Manado, 2018)
This paper aims to describe the implementation of the Broadcasting Act as a policy of multicultural communication in Indonesian television. This is the government's attempt to control foreign cultural imperialism. Through the Broadcasting Act, the Government of Indonesia seeks to protect Indonesian culture and encourage the emergence of multicultural values on Indonesian television. But now local culture on Indonesian television face the hegemony and invasion of foreign cultures. This is relevant with Cultural Imperialism Theory that Western media has dominated the world. In fact, the Indonesian Broadcasting Act faces media capitalism and cultural imperialism. Therefore, the Indonesian Broadcasting Commission and the public need to work together to maintain the value of Indonesian multiculturalism not to be displaced by foreign cultures.Keywords: Multicultural Communication, Broadcasting Act, Television, Cultural Imperialism.